Mortality and years of life lost to suicide in Rio Grande do Norte, Brazil, 2000-2015 - Emelynne Gabrielly de Oliveira Santos; Kelly Graziani Giacchero Vedana; Isabelle Ribeiro Barbosa (Universidade Estadual de Maringá, 2019)
Analyze the epidemiological profile of and years of life lost to suicide in Rio Grande do Norte, Brazil, from 2000 to 2015. This is an ecological study in which data on death were sourced from the Mortality Information System. Years of Potential Life Lost were calculated over the historical series. A total of 2,266 deaths by suicide were analyzed, identified during the period, with the most frequent cases being those occurring at home, by hanging, among men, black people, single people and the elderly. More Years of Potential Life Lost were counted in the economically active age group (30-39 years old). Thus, recognizing the epidemiological characteristics of suicide in Rio Grande do Norte may guide more effective actions and strategies targeting risk populations and reinforces the need for further studies focusing on regions with the highest rates in the state. Moreover, mental health care must be adapted to age and gender, besides approaching social support needs and feeling of belonging.